2021
DOI: 10.1007/s11060-021-03918-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated baseline C-reactive protein levels predict poor progression-free survival in sporadic vestibular schwannoma

Abstract: Background Recent investigations showed emerging evidence of the role of inflammation in the growth of sporadic vestibular schwannoma (VS). The present retrospective study investigated the impact of systemic inflammation on tumor progression using serum C-reactive protein (CRP) levels in a series of 87 surgically treated sporadic VS patients. Methods The optimal cut-off value for CRP was defined as 3.14 mg/dl according to the receiver operating characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have for example demonstrated elevated neutrophil-to-lymphocyte ratio, a systemic marker of inflammation, in patients with growing VS, 34 and decreased progression-free survival in patients with a high baseline serum CRP (≥3.14 mg/dL) level at the time of VS diagnosis. 35 In keeping with the dense infiltration of tumor-associated macrophages seen in growing VS, studies have also shown upregulation of numerous monocytic cytokines in the plasma of patients with growing VS. 14 Evidence that sporadic VS can have widespread effects remote to the tumor also comes from studies of SNHL in affected patients, with emerging evidence that direct damage to cochlea hair cells may occur through factors secreted into the CSF or blood by the tumor such as MMP-14 and the pro-inflammatory cytokine TNFα. 4 , 5 , 36 There has to date, however, been no assessment of VS induced inflammatory changes within the brain parenchyma itself.…”
Section: Discussionmentioning
confidence: 81%
“…Recent studies have for example demonstrated elevated neutrophil-to-lymphocyte ratio, a systemic marker of inflammation, in patients with growing VS, 34 and decreased progression-free survival in patients with a high baseline serum CRP (≥3.14 mg/dL) level at the time of VS diagnosis. 35 In keeping with the dense infiltration of tumor-associated macrophages seen in growing VS, studies have also shown upregulation of numerous monocytic cytokines in the plasma of patients with growing VS. 14 Evidence that sporadic VS can have widespread effects remote to the tumor also comes from studies of SNHL in affected patients, with emerging evidence that direct damage to cochlea hair cells may occur through factors secreted into the CSF or blood by the tumor such as MMP-14 and the pro-inflammatory cytokine TNFα. 4 , 5 , 36 There has to date, however, been no assessment of VS induced inflammatory changes within the brain parenchyma itself.…”
Section: Discussionmentioning
confidence: 81%
“…Kaplan-Meier estimates were used to visualize the probability of PFS in either MIB-1 and MC groups. To evaluate the time-varying performance of MIB-1 and MC on PFS time-dependent ROC analysis was conducted using the R package "risksetROC" of the R software (version 4.0.4; R Foundation for Statistical Computing, Vienna, Austria) [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…A shortened progression-free survival has also been reported for sporadic vestibular schwannoma patients with notably elevated baseline CRP (approx. > 31 mg/L), and hsCRP has been associated with poor cognitive function in acoustic neuroma [ 871 , 872 ]. Additionally, an interesting study found that cases with craniopharyngiomas and Rathke’s cleft cysts had higher CRP than those with pituitary adenomas, revealing their higher systemic inflammation [ 873 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%